Teachers’ Perspective towards Platform Merdeka Mengajar in Implementing Kurikulum Merdeka - Hulu, Jernih Permata Sari; Telaumbanua, Yasminar Amaerita; Zega, Riswan; Waruwu, Yaredi (research, training and philanthropy institution Natural Aceh, 2025)
The purpose of this study was to describe teachers' perspectives towards Platform Merdeka Mengajar in implementing kurikulum merdeka and to find out how the teachers follow the developments of Platform Merdeka Mengajar at SMP Negeri 2 Tugala Oyo. This research is qualitative. Respondents consisted of three teachers at SMP Negeri 2 Tugala Oyo, namely an English teacher, an Indonesian teacher, and a Math teacher. Data was collected through interviews, supported by documentation. All data was collected and analyzed descriptively to obtain reliable findings. In implementing kurikulum merdeka, Kemendikbudristek developed the Platform Merdeka Mengajar to make it easier for teachers to teach according to students' abilities, provide training to improve competence and work to inspire peers. The results of the study showed that: (1) the teachers' perspective about Platform Merdeka Mengajar in implementing Kurikulum merdeka is positive and appreciated because this platform helped and supported the teachers' implementing kurikulum merdeka at SMP Negeri 2 Tugala Oyo, (2) the teachers have several ways to follow the developments of Platform Merdeka Mengajar (PMM) namely, the teachers must be able to access all the features available in the application because by always accessing these features, teachers can find out what developments are available in the application.